PENGARUH ETOS KERJA KRISTEN TERHADAP KINERJA PEKERJA DI GEREJA BETHEL INDONESIA TABGHA BATAM - George Rudi Hartono Pasaribu (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
To improve service excellence, full-time workers must pay attention to their performance. It is a quality work ethic and high performance that is needed by the Church to achieve a high quality of service. A very significant role in realizing performance is ourself, if a full-time worker in a church has a high Christian work ethic then he can have a positive influence on those around him. Full-time workers who have noble thoughts about their work can work with full trust, sincerity, responsibility and do everything as for God. This study aims to conduct a theoretical test of the influence of the Christian work ethic on the performance of full-time workers at the Secretariat of the Indonesian Bethel Church Tabgha Batam. To test the effect of the Christian work ethic variable on performance, multiple linear regression analysis was used by distributing 92 questionnaires to full-time workers. After analyzing the results obtained R square 0.387 with a significance <0.05, which means that work ethic has a positive influence on performance of 38.7%.